Exploration of the Phytochemical Constituents in Honey from Southwestern Nigeria (e-Proceedings of the Faculty of Agriculture International Conference, 2025)
Honey is a product of bees (Apis mellifera); it is nutritional, a source of income, and medicinal. The high demand for honey has necessitated curious research into the importance of this cherished resource. Its insufficient production makes it scarce and exorbitant. However, this paper assesses honey quality in light of its possession of phytochemical compounds and its relevance to livestock and human health in Southwestern Nigeria (SN). Using a multistage sampling procedure, Oyo, Ogun, and Osun states were selected purposively based on their prevalent honey production activities. Three localities were later chosen per state. Each of the localities: Aba Oka, Oke Onitii, Iyemogun, Iwoye, Alabata, Ijagun, Oke Orogun, Laniba and Badeku were selected from a senatorial district for even sampling distribution. An emergent sampling technique was employed to obtain capped honeycomb from one hive per locality. Honey was harvested between October and April and was used for phytochemical constituents’ analysis using standard procedures. Data were analysed using descriptive statistics. In Oyo, Ogun, and Osun states, phytochemicals (Saponin, Tannin, Flavonoid, Steroid, Terpenoid, Coumarin, Chalcones, Quinone, Alkaloid, Cardiac Glycosides, Phenols and Protein) were confirmed in all the honey samples except few (Anthocyanins and Emodin) that were affirmed absent. However, Di-terpenes were present in all honey samples except Ijagun and Oke Orogun honey. Conclusively, SN honey was affirmed to contain phytochemicals that could dislodge free radicals responsible for livestock and human ailments. This assures a solution to poor health observed in livestock and humans.